Efficient laboratory perovskite solar cell recycling with a one-step chemical treatment and recovery of ITO-coated glass substrates - Le Khac D.; Chowdhury S.; Soheil Najm A.; Luengchavanon M.; mebdir Holi A.; Shah Jamal M.; Hua Chia C.; Techato K.; Selvanathan V. (Elsevier Ltd, 2025)
The proliferation of organic?inorganic perovskite solar cells (PSCs) has garnered considerable attention due to their potential for low-cost, large-scale photovoltaic panel production. However, the inclusion of lead in PSCs poses significant sustainability challenges, necessitating effective end-of-life treatment strategies to mitigate environmental pollution and comply with electronic waste disposal regulations. In this study, we present a novel recycling system for decomposing and reclaiming the constituent materials of a typical PSC. Utilizing a one-step solution process extraction approach, we successfully preserved the chemical composition of each layer, enabling their potential reuse. This recycling method not only addresses the separation of the toxic lead component but also emphasizes the recovery of other valuable PSC layers. Notably, the commonly used hole transport layer in perovskite solar cells is Spiro-OMeTAD, which was successfully extracted with chlorobenzene, with its purity subsequently confirmed. Moreover, the removal of individual layers facilitated the retrieval of indium-doped tin oxide (ITO) conductive glass, a critical substrate in PSC fabrication. Comparative analysis of the physical and electrical properties of recycled and reference ITO substrates revealed minimal discrepancies, indicating the feasibility of reusing recycled substrates without compromising device performance. The proposed recycling technique offers a practical approach to mitigate pollution risks, minimize waste generation during the recycling process of perovskite-based solar cells, and reduce end-of-life recycling costs. ? 2023